Geographical Variation and Social Work Students' Job Intentions in China: A Geographic Information Systems Approach. Issue 2 (2nd February 2018) - Wang, Yean; Guo, Yingqi; Zeng, Shouchui
Abstract: Social work education in China is undergoing far-reaching development. However, an important issue, low professional commitment, has been identified. Why do social work graduates—especially master's level graduates—take jobs unrelated to social work? To answer this question, it is important to take into account that the professionalization of social work is happening unevenly across China as a result of uneven social and economic development. Models used in past research do not consider the possibility that the low intention for social work jobs and its potential predictors may vary across regions. To address this problem, Geographic Information Systems software is being adopted to explore the varying degrees of social work graduates' job intention, its predictors across China, and the association between job intention and predictors at both national and regional levels. Authors of this study found substantial geographic variation in predictors of social work graduates' job intention across regions. Their findings also suggest some heterogeneity in the association between job intention and specific correlates that would be masked in the traditional nationwide model. Policymakers aiming to improve the job intention of social work graduates should consider regional variation as part of their approach.